Hubungan Kepadatan Tanah Terhadap CBR Labor Di Perumahan Eka Jaya Permata II Kota Payakumbuh - Asnur, Hanifah; Sari, Ridha; Yunita, Rini (Universitas Andalas, 2024)
Soil density is closely related to determining the design CBR on road pavements. In this study, soil density testing used standard proctor test methods (ASTM D-698) to obtain the optimum water content (w) and maximum dry weight (γ_d). This study obtained an optimum water content of 24.72% and a maximum dry weight of 1.61 gr/cmᶟ. Meanwhile, for the CBR labor test, the water content obtained from the results of the previous soil density test was used, while for the CBR labor test based on the ASTM D-1883 standard with 3 test samples, namely 10 impacts, 25 impacts and 56 impacts. From the results of the CBR labor obtained at a decrease of 0.1 inches with 10 impacts was 7, for 25 impacts it was 8.74 and 56 impacts it was 9.81. This value is used to determine the design CBR value which is associated with 95% maximum dry weight on soil compaction, the value is 9.6%. This value, if adjusted according to pavement standards, is included in the fairly good category of soil and can be used for sub-base on the pavement of the Eka Jaya Permata II housing complex in Payakumbuh City.